Smoking cessation and diabetes control in Kerala, India: an urgent need for health education - C.U. Thresia, K.R. Thankappan and M. Nichter (HEALTH EDUCATION RESEARCH March 30, 2009, 2009)
This study documented the tobacco use among male diabetes patients in a clinic-based population of urban India, patient reports of physician cessation messages and patients' perception of tobacco use as a risk factor for diabetes complications.All the 444 male diabetes patients who attended three public sector hospitals inThiruvananthapuram district, Kerala, were surveyed to ascertain their tobacco use as well as the frequency and content of quit messages received from health staff. A significant proportion (59 per cent) of diabetes patients were tobacco users prior to diagnosis and more than half of them continued to use tobacco, many daily,even after diagnosis. Of the 100 current smokers, 75 per cent were asked about their tobacco use at the time of diagnosis; of those, 52 per cent were advised to quit. However, a lack of patient awareness existed regarding the linkages of smokingand diabetes complications. Notably, 52 per cent of patients did not associate smoking with diabetes complications. Given the magnitude of tobacco use among diabetics, there is clearly a need for more proactive cessation efforts. The times of illness diagnosis, illness flare-ups and emerging illness complications are teachable moments when patients are primed to change their behavior and more motivated to quit tobacco.